Photothermal behaviour of titanium nitride nanoparticles evaluated by transient X-ray diffraction. Issue 4 (26th January 2021) - Diroll, Benjamin T.; Brumberg, Alexandra; Leonard, Ariel A.; Panuganti, Shobhana; Watkins, Nicolas E.; Cuthriell, Shelby A.; Harvey, Samantha M.; Kinigstein, Eli D.; Yu, Jin; Zhang, Xiaoyi; Kanatzidis, Mercouri G.; Wasielewski, Michael R.; et al.
Abstract : Metal nitrides are a promising non-toxic, inexpensive, and durable material for photothermal applications. The photothermal properties of titanium nitride are measured using time-resolved X-ray diffraction following optical excitation. Abstract : The photothermal properties of metal nitrides have recently received significant attention owing to diverse applications in solar energy conversion, photothermal therapies, photoreactions, and thermochromic windows. Here, the photothermal response of titanium nitride nanoparticles is examined using transient X-ray diffraction, in which optical excitation is synchronized with X-ray pulses to characterize dynamic changes in the TiN lattice. Photoinduced diffraction data is quantitatively analyzed to determine increases in the TiN lattice spacing, which are furthermore calibrated against static, temperature-dependent diffraction patterns of the same samples. Measurements of 20 nm and 50 nm diameter TiN nanoparticles reveal transient lattice heating from room temperature up to ∼175 °C for the highest pump fluences investigated here. Increasing excitation intensity drives sublinear increases in lattice temperature, due to increased heat capacity at the higher effective temperatures achieved at higher powers. Temporal dynamics show that higher excitation intensity drives not only higher lattice temperatures, but also unexpectedly slower cooling of the TiN nanoparticles, which is attributed to heating of the solvent proximal to the nanoparticle surface.